Qira’at Al-Qur’an - Jihan Zahirah Rasyidah; Arinatun Najah; Ahmad Muzaqi; Hakmi Hidayat (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Qiraat al-Quran is a branch of science that studies the various methods of reading the Qur'an obtained from the Prophet Muhammad SAW through reliable channels. The purpose of this study is to reveal the meaning of Qiraat, establish the correct systematic rules regarding Qiraat, explain the various levels in Qiraat, describe the types of Qiraat, and explain the reasons behind the differences that exist, as well as highlight the significance of the study of this field. The results of the study indicate that a recognized Qiraat must meet three main requirements: in line with the rules of correct Arabic, in accordance with the rasm Uthmani, and have a valid sanad. Differences in Qiraat arise as a result of history and varying dialects among the Companions. Studying Qiraat is very important to maintain the authenticity of the Qur'an, deepen the meaning of its verses, and avoid fanaticism towards a particular reading method.